2017
DOI: 10.15171/jcvtr.2017.07
|View full text |Cite
|
Sign up to set email alerts
|

The association of right coronary artery conus branch size and course with ST segment elevation of right precordial leads and clinical outcome of acute anterior myocardial infarction

Abstract: Introduction: Coronary artery disease is the leading cause of death worldwide and electrocardiogram (ECG) is a reliable diagnostic tool to determine a myocardial infarction. The present study tried to compare the relationship between the ECG findings and angiographic findings in patients with acute anterior myocardial infarction. Methods: Seventy-four patients with acute anterior ST elevation myocardial infarction (Ant- STEMI) presenting to the emergency room in the first 12 hours after the onset of symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the Figure, A, however, ST-segment elevation is absent in V 1 . There may be 3 plausible explanations: acute total LMT occlusion without collateral circulation, multiple blood supply in lead V 1 , and secondary ST-T wave changes . (1) In 2012, Fiol et al first reported the STEMI pattern with RBBB and left anterior fascicular block of proximal LAD without ST-segment elevation in lead V 1 , suggesting acute total occlusion of LMT without collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Figure, A, however, ST-segment elevation is absent in V 1 . There may be 3 plausible explanations: acute total LMT occlusion without collateral circulation, multiple blood supply in lead V 1 , and secondary ST-T wave changes . (1) In 2012, Fiol et al first reported the STEMI pattern with RBBB and left anterior fascicular block of proximal LAD without ST-segment elevation in lead V 1 , suggesting acute total occlusion of LMT without collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reciprocal ST-segment depression in lead V 1 caused by left circumflex branch was excluded. (2) The basal portion of the interventricular septum may be supplied with blood by the septal branches and the conus branch of LAD and the conus branch of the right coronary artery . Accordingly, in patients with proximal LAD occlusion, the presence of the large conus branches may protect the interventricular septum, which manifests with absence of ST-segment elevation in lead V 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies demonstrated a relatively high incidence of concurrent RV infarction in patients with anterior STEMI (Barsheshet et al, 2011;Bodi et al, 2010;Pourafkari et al, 2016;Tusun et al, 2015). However, less data have been reported about the prognostic importance of STE in lead V 4 R in patients with anterior STEMI and authors are in conflict on how this STE has an impact on the prognosis (Barsheshet et al, 2011;Bodi et al, 2010;Ghaffari, Taban Sadeghi, & Sayyadi, 2017;Tusun et al, 2015). Additionally, RV infarction is considered as temporary and final infarct size is considered as small due to its thinner wall and subendocardial oxygenization (Bodi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%